Analysis of linear wave power generator model with real sea experimental results. Issue 5 (1st September 2013) - Krishna, Remya; Svensson, Olle; Rahm, Magnus; Kottayil, Sasi K.; Waters, Rafeal; Leijon, Mats
Abstract : This study presents the dynamic modelling of a linear permanent magnet generator for extracting energy from ocean waves. Translator position, calculated from measured generator voltage, is used as input for the simulation model. Instantaneous power from the simulation model has been compared with the measurements from the Lysekil research site. The power output from the model considering the air gap flux variation is precisely matching with the measured values before core saturation. The generator dynamic model is modified by including the saturation effect. Although a simple mathematical expression is considered for representing the saturation, the model gives accurate power spectrum close to the experimental results. The presented model is a first step towards the system model that can simulate the entire electric system including electric grid. As such, the generator model can be used for further analysis of the wave energy conversion system.